Systemic Necrotizing Vasculitis in Sheep Is Associated With Ovine Herpesvirus 2. Issue 1 (January 2019) - Pesavento, Patricia A.; Dange, Rahul B.; Ferreras, M. Carmen; Dasjerdi, Akbar; Pérez, Valentin; LaRoca, Anna; Silván, Julio Benavides; Diab, Santiago; Jackson, Kenneth; Phillips, Ida L.; Li, Hong; Cunha, Cristina W.; et al.
Ovine herpesvirus 2 (OvHV-2) is one of the gammaherpesviruses in the genus Macavirus that can cause malignant catarrhal fever (MCF) in ungulates. Sheep are the adapted host for OvHV-2 and it is generally assumed that infection is not associated with disease in this species. However, cases of "polyarteritis nodosa" or idiopathic systemic necrotizing vasculitis reported in sheep are similar to vascular lesions in clinically susceptible species with MCF. Using a recently developed in situ hybridization (ISH) method, we were able to identify OvHV-2 nucleic acids within lesions and correlate the viral distribution with systemic necrotizing vasculitis in 9 sheep, including both naturally and experimentally OvHV-2–infected animals. ISH, combined with polymerase chain reaction and histology, identify OvHV-2 as the likely agent responsible for sporadic, MCF-like vascular disease in sheep.